Human Capital on the European Labour Market - Marzena Kacprzak; Agnieszka Król; Izabela Wielewska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Efficient use of human capital and taking care of its quality in the global labour market is becoming a priority. This is primarily due to the need to function in a multicultural environment, growing competition and population aging. This article is an attempt to systematise knowledge about human capital and its use in the labour market. Attention is being drawn to the effective use of capital, including implementation of European strategies, as well as trends and challenges facing key employment issues. In addition, an effort has been made to identify key employee competencies reflecting global labour market trends. The article shows the importance of quality and investment in human resources, which is associated with the use of EU projects and programmes targeted at young people on the labour market.